If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -36 = -10y + 7 Reorder the terms: -36 + 9y = -10y + 7 Reorder the terms: -36 + 9y = 7 + -10y Solving -36 + 9y = 7 + -10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10y' to each side of the equation. -36 + 9y + 10y = 7 + -10y + 10y Combine like terms: 9y + 10y = 19y -36 + 19y = 7 + -10y + 10y Combine like terms: -10y + 10y = 0 -36 + 19y = 7 + 0 -36 + 19y = 7 Add '36' to each side of the equation. -36 + 36 + 19y = 7 + 36 Combine like terms: -36 + 36 = 0 0 + 19y = 7 + 36 19y = 7 + 36 Combine like terms: 7 + 36 = 43 19y = 43 Divide each side by '19'. y = 2.263157895 Simplifying y = 2.263157895
| -16f+1=-17f+16 | | c-0.25c=25 | | -8d=11d+19 | | 4z^2=x^2+y^2 | | 1.35=1.85(b+-13)+14.3 | | -0.4=1.6(w+2)-0.4 | | -0.99(h-7)=-7.92 | | Xsquared+ysquared=153 | | -3(d-8.8)=6.3 | | 31(m-963)+63=931 | | 4x-12=20-4x | | 59=4x+27 | | 23000=10x | | a+3+2=-1+3a+4 | | 5x+21=2x+3 | | solvex+5=20-4x | | -x^3+9x^2+x-105=0 | | 8000*12=3000+(3000+x)+(3000+2x)+(3000+3x)+(3000+4x)+(3000+5x)+(3000+6x)+(3000+7x)+(3000+8x)+(3000+9x)+(3000+10x)+(3000+11x) | | x^3+9x^2+11x-34=-3x-10 | | 96000=3000+(3000+x)+(3000+2x)+(3000+3x)+(3000+4x)+(3000+5x)+(3000+6x)+(3000+7x)+(3000+8x)+(3000+9x)+(3000+10x)+(3000+11x) | | 2h+2s=3.50 | | 10=3x+12y | | 2.5(a+4)-3.2=43 | | 15x^4-10x^2=0 | | t-13=35 | | 5760000=x*(x+50) | | 4w-4=2w-11 | | 6.6+6n=7n-0.4 | | 2x+1=x+37 | | -104=8i | | 30x+(20-x)x=100 | | h-9=-13 |